Work Practices to Manage Bump Prone Ground - Floyd Varley (International Conference on Ground Control in Mining, 2008)
In deep and highly-stressed coal mining, advanced design practices are used to minimize the potential for damaging events to occur. Despite these design efforts, the hazard of coal mine bumps can not be completely eliminated. This paper will review current and historic work practices used internationally to minimize the hazard to miners from mining in conditions which could produce a bump. These site specific work practices have a common base in monitoring for conditions which could result in a bump and application of controls to prevent the occurrence or minimize the severity of an event where miners are working. Monitoring practices range from purely observational to semi quantitative. Control methods attempt to initiate events in a controlled manner, absorb the energy of a potential event or reduce the potential for or magnitude of an event by altering the stress conditions of the mine workings. Building from the experiences of other coal fields, an empirical framework to manage the potential hazard of coal mine bumps can be developed to enhance the level of safety provided by prudent mine design.